Cover Picture: Nitrogen‐Doped Nanoporous Carbons through Direct Carbonization of a Metal‐Biomolecule Framework for Supercapacitor (Chin. J. Chem. 2/2016). Issue 2 (February 2016) - Zhang, Jianhui; Zhang, Daliang; Dai, Guanghui; Fang, Qianrong; Qiu, Shilun
Abstract : The cover picture is composed by an assumptive structure model of nitrogen‐doped porous carbons synthesized by direct carbonization of a nitrogen‐rich zinc glutamate metal‐ biomolecule framework. The background is made from an experimental transmission electron microscopy image. This cover picture illustrates that gas molecules and metal components released by the help of heating and chemical treatments, forming nitrogen‐doped porous carbons. These carbons exhibited high specific surface areas (up to 1619.2 m 2 /g) and also a large specific capacitance of 140.8 F/g at a current density of 0.25 A/g. More details are discussed in the article by Qiu et al . on page 203–209.